The Social Base of New Authoritarianism in Southeast Asia: Class Struggle and the Imperial Mode of Living - Schaffar, Wolfram (2018)
Abstract: This research note addresses the question of the social base of new authoritarianism and sketches out new directions for future research. In Europe and the United States, this question has led to highly controversial debates between two camps. One side argues for a class analysis and sees a revolt of the disenfranchised and poor behind the electoral success of the right-wing populists. The other side draws on the concept of the Imperial Model of Living and focuses on a cross-class alliance in the North, defending their unsustainable consumption pattern, which rests on the exploitation of resources, sinks, and cheap labor from the South. It will be argued that a view from Southeast Asia - especially data from Thailand and the Philippines - has the potential to challenge some assumptions of this debate and add important insights. Here, a rising middle class has been in the focus of the debate on democratization in the 1980s/1990s. Starting with the Asia Crisis in 1997/1998, the rise